2016
DOI: 10.3390/s16060880
|View full text |Cite
|
Sign up to set email alerts
|

Design, Fabrication, Simulation and Characterization of a Novel Dual-Sided Microelectrode Array for Deep Brain Recording and Stimulation

Abstract: In this paper, a novel dual-sided microelectrode array is specially designed and fabricated for a rat Parkinson’s disease (PD) model to study the mechanisms of deep brain stimulation (DBS). The fabricated microelectrode array can stimulate the subthalamic nucleus and simultaneously record electrophysiological information from multiple nuclei of the basal ganglia system. The fabricated microelectrode array has a long shaft of 9 mm and each planar surface is equipped with three stimulating sites (diameter of 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Similar electricalc omponents may also be adapted to perform other functions, such as pH and oxygen sensing, [140] and electrical stimulation. [141,142] Furthermore, microfabrication will open an opportunityf or monolithic integration of electrochemical probesw ith microfluidic and opticalm odalities (see below). A variety of substrates and materials has been used in development of the microfabricated probesw ith the goal of creating small, biocompatible devices with enhanced sensor sensitivity and selectivity.H owever, the current technology stillh as al imitation in an umber of measurable neurochemicals (less than 10 compounds can be measured).…”
Section: Discussionmentioning
confidence: 99%
“…Similar electricalc omponents may also be adapted to perform other functions, such as pH and oxygen sensing, [140] and electrical stimulation. [141,142] Furthermore, microfabrication will open an opportunityf or monolithic integration of electrochemical probesw ith microfluidic and opticalm odalities (see below). A variety of substrates and materials has been used in development of the microfabricated probesw ith the goal of creating small, biocompatible devices with enhanced sensor sensitivity and selectivity.H owever, the current technology stillh as al imitation in an umber of measurable neurochemicals (less than 10 compounds can be measured).…”
Section: Discussionmentioning
confidence: 99%
“…These four sites with diameter of 50 μm and the other four recording sites were also mutually spaced with equal center-to-center distance of 250 μm. Figure 1 showed the schematic diagram of the designed microelectrode array, and design and fabrication of the probes have been described in detail elsewhere [67]. In this paper, the in vivo neural recording and electrochemical performance of recording sites modified by rough-surfaced AuPt alloy nanoparticles were mainly studied.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, in order to improve the in vivo neural recording performance of our fabricated Michigan type silicon electrodes [67], we modified the round-shaped gold microelectrode sites (diameter of 20 μm) via electro-co-deposition of Au-Pt-Cu alloy nanoparticles followed by chemical dealloying Cu for the first time. Firstly, the prepared rough-surfaced Au-Pt alloy nanoparticles were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD), which showed that the prepared AuPt alloy nanoparticles exhibited cauliflower-like shapes and possessed very rough surfaces with many different sizes of pores.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed description of the design and fabrication of the microelectrode arrays was given in our group's previous work. (35) In this study, the neurotransmitter measurement sites with diameter of 50 μm were modified with Nafion film/ nanoporous AuPt nanoparticles used as DA sensors and their performance was mainly studied. …”
Section: Fabricated Microelectrode Arraysmentioning
confidence: 99%
“…Here, in order to construct in vivo DA electrochemical sensors on Michigan-type silicon electrodes fabricated by our group, (35) …”
Section: Introductionmentioning
confidence: 99%